Pengelolaan Sistem Syari’ah dalam Meningkatkan Jumlah Unit Usaha di Pesantren At-Tahdzib Jombang - Asyarurahim; Febi Ambarwati (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2024)
Islamic boarding school is an institution that has a lot of potential, including economic potential. To increase this potential is a challenge for Islamic boarding schools so that they can improve the economic welfare of the Islamic boarding school itself and the wider community. The spirit of independence that is formed by students can be a potential for Islamic boarding schools to increase the economic stability of Islamic boarding schools. One of the efforts to make the Attahdzib Islamic boarding school independent is through business units. Where a well-organized business will provide output with good income. In today's era of free competition, building the competency and capacity of students is a must. Many Islamic boarding schools have tried to develop productive economic activitiesThe existence of these various business units is a means of education in the fields of independence, entrepreneurship, sincerity and sacrifice Based on the limitations and identification of problems that have been determined, the formulation of the problem is how is the management applied by sharia business units in increasing the number of business units in the At-Tahdzib Islamic boarding school? The problem approach used in this study is to use a type of field research where data is obtained from the field directly from the source, so that the data sources in field research are primary and secondary sources. Through a qualitative approach, namely research used to research natural or natural social life. Based on the results of the presentation and analysis of data, the author obtained a conclusion that can be drawn from the research on